PENERAPAN COOPERATIF LEARNING TIPE TEAM ASSISTED INDIVIDUALIZATION UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Hardiana, Nanang (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the extent of the influence of the application of the Team Assisted Individualization type cooperative learning model () on improving student learning outcomes and the ability of teachers to make learning plans and carry out the learning process through the application of the Team Assisted Individualization type cooperative learning model (). The study was conducted in 2 cycles with two meetings for each cycle. The subject of the study was students of class X TKR 1 SMKN 1 Cijulang. The material taken in this study is the material Functions sub-chapters Composition and Inverse functions. The number of students is 36 people, research instruments in the form of written tests and observation sheets (observations) of learning activity plans and activities of teachers and students during the implementation of learning. Data analysis was carried out in each learning cycle using triangulation, saturation and colding / labeling stages. The conclusions of the study showed that there was an increase in the ability of teachers to make plans for learning activities in the second cycle. The observation results showed that the average value in cycle 1 was 279 or 69.75% while cycle 2 was 300 or 75%. The observation results for the teacher's ability to manage learning activities, in cycle 1 amounted to 66.4% and in cycle 2 amounted to 74.22%. So it can be said that there is an increase in the ability of teachers to carry out the learning process through the application of a Team Assisted Individualization () type cooperative learning model. In addition, the Cooperative Learning Type Team Assisted Individualization () learning model can improve student learning outcomes, this can be seen from the results in cycle I the average student score of 70, in cycle II it increases to 80